PERAN PERAWAT DALAM MONITORING ANTIHIPERTENSI PADA PENDERITA HIPERTENSI - Siti Muflihah; Nurul Kamariyah (Jurnal Ilmiah Kesehatan, 2013)
Hypertension or high blood pressure is a common condition in which the force of the blood against your artery walls is high. Hypertension etiology is classified as either primary (essential) hypertension or secondary hypertension. Uncontrolled high blood pressure increases your risk of serious health problems, coronary artery disease, heart failure, stroke, and kidney disease. The main goal of antihypertensive drugs is to lower blood pressure to less than 140/90 or even lower so there is no more severe complications. Nurses have an important role to antihypertensive treatment because nurses are the most widely associated with patients directly and continuously. Nurses can monitor therapeutic effects and side effects of treatment antihipertensi